2021
DOI: 10.1155/2021/5459432
|View full text |Cite
|
Sign up to set email alerts
|

Conversion Surgery for Patients with Advanced Gastric Cancer with Peritoneal Carcinomatosis

Abstract: Background. Patients with advanced gastric cancer (AGC) with peritoneal carcinomatosis (PC) usually have poor outcomes and high mortality risk, even with cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC). This study analyzed the prognostic factors of AGC with PC and evaluated laparoscopic HIPEC (LHIPEC) plus neoadjuvant intraperitoneal and systemic chemotherapy (NIPS) as a conversion surgery for AGC patients with PC with a poor initial prognosis. Patient and Methods. We retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Although the impact of HIPEC on prognosis was not observed in our study, HIPEC still plays an irreplaceable role in patients with gastric cancer. A study in China showed that HIPEC signi cantly improved the OS and treatment of malignant ascites in patients with gastric cancer with initially higher PCI scores and positive peritoneal lavage uid with peritoneal metastasis (P < 0.001) [5]. This was also con rmed by a multicenter study in Spain [6,7].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Although the impact of HIPEC on prognosis was not observed in our study, HIPEC still plays an irreplaceable role in patients with gastric cancer. A study in China showed that HIPEC signi cantly improved the OS and treatment of malignant ascites in patients with gastric cancer with initially higher PCI scores and positive peritoneal lavage uid with peritoneal metastasis (P < 0.001) [5]. This was also con rmed by a multicenter study in Spain [6,7].…”
Section: Discussionmentioning
confidence: 72%
“…Although HIPEC is frequently used in the treatment of peritoneal metastases from abdominal malignancies, such as gastric cancer [4], HIPEC has an irreplaceable role in patients with malignant ascites. A study in China showed that HIPEC signi cantly improved the overall survival (OS) and treatment of malignant ascites in patients with gastric cancer with initially high peritoneal carcinoma index (PCI) scores and positive peritoneal lavage uid with peritoneal metastasis (P < 0.001) [5]. This result was con rmed by multicenter studies in Spain [6,7].…”
Section: Introductionmentioning
confidence: 92%
“…Although the impact of HIPEC on prognosis was not observed in our study, HIPEC still plays an irreplaceable role in patients with gastric cancer. A study in China showed that HIPEC significantly improved the OS and treatment of malignant ascites in patients with gastric cancer with initially higher PCI scores and positive peritoneal lavage fluid with peritoneal metastasis ( P < 0.001) [ 5 ]. This was also confirmed by a multicenter study in Spain [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although HIPEC is frequently used in the treatment of peritoneal metastases from abdominal malignancies, such as gastric cancer [ 4 ], HIPEC has an irreplaceable role in patients with malignant ascites. A study in China showed that HIPEC significantly improved the overall survival (OS) and treatment of malignant ascites in patients with gastric cancer with initially high peritoneal carcinoma index (PCI) scores and positive peritoneal lavage fluid with peritoneal metastasis ( P < 0.001) [ 5 ]. This result was confirmed by multicenter studies in Spain [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…59 Lee et al found that patients who underwent L-HIPEC + NIPS followed by CRS-HIPEC had a better mean overall survival compared to those who only underwent CRS-HIPEC, chemotherapy or palliative care. 60 Laparoscopic HIPEC (L-HIPEC) Given the high morbidity associated with combining HIPEC and CRS, there has been an effort to administer HIPEC in a minimally invasive fashion, so as to decrease the associated morbidity. First published by Yonemura in 2016, other groups have shown that L-HIPEC was well tolerated and could reduce PCI score.…”
Section: Port-based Approachesmentioning
confidence: 99%